STUDI PENGARUH PENAMBAHAN YTTRIUM DAN PERLAKUAN PANAS BETA TERHADAP KETAHANAN HIDROGEN PADUAN ZIRCALOY-4-0,1%Mo PADA TEMPERATUR 600°C DAN 800°C - Alfatar, Ajra; Basuki, Eddy Agus; Prajitno, Djoko Hadi (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
Electrical energy is a source of energy that is widely used and needed by humans. So that the need for electrical energy will increase along with the increase in the human population. Nuclear Power Plant is one solution to this problem. One of the important components of nuclear reactors, namely nuclear fuel cladding, usually uses a material in the form of a zirconium alloy, but the use of this alloy for a long time will be susceptible to embrittlement due to hydrogen penetration. A series of experiments were conducted to determine the effect of adding yttrium and beta heat treatment on hydrogen resistance and mechanical properties of Zircaloy-4-0.1%Mo-xY alloy (x=0 wt%; 0.5 wt%; 1 wt%). The addition of yttrium causes an increase in the amount of precipitate which is thought to be α-Y while increasing the alloy hardness in both as cast alloys and beta heat treatment. Beta heat treatment decreased the alloy hardness due to an increase in the number of β-Zr phases. Hydrogen resistance can be increased by adding yttrium because it acts as a β-Zr phase stabilizer. Similarly, beta heat treatment can increase hydrogen resistance with the same method, namely increasing the number of β-Zr phases so that the amount of soluble hydrogen increases. The addition of 1 wt% Y to zircaloy-4-0.1%Mo alloy with beta heat treatment showed the best hydrogen resistance with a thickness of 6.24 μm at 600°C and 545.5 μm at 800°C.